MUSIK SEBAGAI MEDIA SELF HEALING - Fredho Umbu Wara Kasedu, Firmanto Adi Nurcahyo (JURNAL TALENTA PSIKOLOGI, 2024)
Self healing is a simple method that can be done by someone in order to heal their own wounds. From a self-healing point of view, basically every body can carry out a natural process to get healing, music is only a medium to help that process. It was found that music in the world of therapy proved to be very useful and effective so that it was concluded that all types of music used would affect a person's condition by taking into account the listener's background and interest in the music.